Contamination composition of Fe, Mn and Al at 8 different profiles of solid waste disposal areas in Malaysia - Othman, Rashidi; Mat Ali, Qurratu Aini; Ramya, Razanah (IACSIT Press, 2016)
Solid waste is a major issue in environmental management as it was generated by almost every single person in the world. In Malaysia, it is estimated 0.8 kg solid waste dumped by one person in rural area and 1.5 kg by person in urban area in a day. Landfill as a final waste disposal point is currently in critical number where it keeps on increasing every year. The most serious issues is landfill may cause air, water and soil pollution as waste disposed at landfill may produce leachate through water runoff at the area. Hence, this research aimed to assess the contamination level of three types of heavy metal which are Iron, Manganese and Aluminum (Fe, Mn, Al) at 8 selected contaminated landfill areas in Selangor, Perak and Melaka. As a result, Fe exhibited highly contamination level ranged from 0.15 mg/L to 0.77 mg/L followed by Mn ranged from 0.06 mg/L to 0.57 mg/L and the lowest is Al ranged from 0.04 mg/L to 0.08 mg/L. Interestingly Perak solid waste disposal area was found to have the highest Fe content (0.77 mg/L), substantially higher than all other areas tested. In contrast Mn was detected highest (0.57 mg/L) in Selangor landfill area. There was positive relationship between type and total content of heavy metals and location of landfill area. Therefore, collaboration and concern from authority and public in managing solid waste may help to reduce the pollution as these types of heavy metal may cause bad impact to the environment and surely human health.